Student Responses to Tolitoli Local Language Learning - Hasia Marto; Karmila Risa Rahmawati Karmila; Dewi Angraini Insiano; Nurul Anisha (Jurnal Ilmiah Sekolah Dasar, 2024)
Students' response to Tolitoli local language learning is one of the important aspects that affect the effectiveness and success of the learning process. In this context, student responses include various attitudes, behaviors and student responses to Tolitoli local language learning. the purpose of this study was to determine student responses in understanding and responding to Tolitoli local language learning which includes students' reactions, attitudes, and feelings towards the material taught and the teaching methods used by teachers during the learning process. This research method uses a mix method, namely qualitative and quantitative approaches with the research subject as many as 39 respondents of grade IV elementary school students. The data collection techniques used were observation, interviews and documentation studies, as well as distributing questionnaires. Data were analyzed using qualitative methods including data collection, data reduction, data presentation, and conclusion drawing. The quantitative method used descriptive statistics. The results of the questionnaire analysis showed a positive response from students to Tolitoli local language learning, with the majority of students expressing satisfaction and understanding the material well. The results of data description concluded that Tolitoli local language learning is very satisfying, although there are some aspects that need to be improved.